Social distancing intentions to reduce the spread of COVID-19: The extended theory of planned behavior - Wignyo Adiyoso; Wilopo (BMC Public Health, 2021)
Abstract Background Due to the absence of a vaccine of SARS-CoV-2 virus pandemic, the most effective way to reduce transmission of the virus is by applying social distancing practices. Exploring factors that determine whether people adopt social distancing measures is, therefore, critical to reducing the spread of the virus. This study aimed to investigate people’s intentions to socially distance based on the extended Theory of Planned Behavior. Methods A questionnaire was distributed to the sample population and collected through social media online and WhatsApp groups from March 26, 2020 to March 29, 2020. There were 823 analyzed out of 1870 responses. The extended TPB variables and risk perception were measured using a 7-point scale (scored from 1 to 7). Data were analyzed using the partial least squares (PLS) structural equation modeling method. Results Study found that the factors influencing the intention to perform social distancing were subjective norms and perceived behavior control. Risk perception affected attitudes, subjective norms, and perceived behavioral control. Media exposure was found to determine attitudes, subjective norms, and risk perceptions. The relationship between attitudes and intentions, and media use and perceived behavior control were not significant. The better and effective risk communication that can change the level of risk perception, raise family and religious leader as well as increase to control behavior are the keys to people’s perform social distancing. Results from a multigroup analysis revealed that younger individuals showed a stronger relationship between the influence of risk perception and PBC and media use on risk perception. The predictive strength of subjective norms from risk perception and risk perception from media use was more strongly associated with rural populations. Conclusions The results of study provide an initial understanding of the level of the public’s risk perception to reduce the spread of SARS-CoV-2. Findings also revealed the role of media use in determining risk perception, attitudes and subjective norms and, in turn, change people’s intention to socially distance. This study may add to the literature of behavioral changes in pandemic and provide a framework for both policymakers and practitioners to formulate effective interventions in the future.